Oxytocin increases the influence of public service advertisements. - Pei-Ying Lin (Public Library of Science (PLoS), 2013)
This paper presents a neurophysiologic model of effective public service advertisements (PSAs) and reports two experiments that test the model. In Experiment 1, we show that after watching 16 PSAs participants who received oxytocin, compared to those given a placebo, donated to 57% more causes, donated 56% more money, and reported 17% greater concern for those in the ads. In Experiment 2, we measured adrenocorticotropin hormone (ACTH) and oxytocin levels in blood before and after participants watched a PSA. As predicted by the model, donations occurred when participants had increases in both ACTH and oxytocin. Our results indicate that PSAs with social content that cause OT release will be more effective than those that do not. Our results also explain why some individuals do not respond to PSAs.